2020
DOI: 10.3390/su12041287
|View full text |Cite
|
Sign up to set email alerts
|

The Life Cycle of Corporate Social Responsibility in Agri-Food: Value Creation Models

Abstract: This paper contributes to the theoretical debate in agri-food economics focusing on corporate social responsibility. Specifically, it aims to define an interpretative model of the processes of social responsibility and value creation in the food industry. An empirical investigation was conducted using an analysis of case studies—representative of sustainable innovation and social responsibility models—as well as in-depth interviews and focus groups with managers of food industries and the sector’s experts. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 51 publications
0
36
0
5
Order By: Relevance
“…As for the purchasing habits, respondents stated to purchase wine directly at the producer. This behaviour suggests that on one hand, the preference of consumers towards local food product characterized by high social benefits [35][36][37][38], whilst on the other hand, their willingness to support the economic growth of local community [39,40]. Further, the study uncovered that consumers spend roughly €10.00 per a bottle of wine and up to €20.00 in wine monthly.…”
Section: Discussionmentioning
confidence: 94%
“…As for the purchasing habits, respondents stated to purchase wine directly at the producer. This behaviour suggests that on one hand, the preference of consumers towards local food product characterized by high social benefits [35][36][37][38], whilst on the other hand, their willingness to support the economic growth of local community [39,40]. Further, the study uncovered that consumers spend roughly €10.00 per a bottle of wine and up to €20.00 in wine monthly.…”
Section: Discussionmentioning
confidence: 94%
“…Socially responsible companies must comply with legal regulations and make additional investment in human capital, the environment and improve their relationships with stakeholders. (Siano et al, 2010;Matei, 2013;Siminica and Sichigea, 2018;Sima and Gheorghe, 2019;Siminica et al, 2015;Nazzaro et al, 2020). In this way, companies are very attentive to the requirements of different categories of stakeholders, given their involvement which are no longer mere spectators of the economic phenomenon, but sanction the inappropriate actions of companies such as those in highly polluting industries or those whose activity has an impact on public health, encouraging their decisions the activity of companies that have adopted the principles of sustainable development.…”
Section: Csr Implication In Agri-food Sectormentioning
confidence: 99%
“…Recently, Triguero, Fernández and Sáez-Martinez [16] proposed the framework in Figure 1 to study the influence of open innovation strategies on the adoption of radical and incremental eco-innovations in this industry. This approach is somehow similar to the framework proposed by Marotta and Nazzaro [59] on the issue of the determinants of value creation processes on farms, and further developed by Marotta and Nazzaro [13] on their recent analysis of value creation in wineries. Triguero et al [16] concluded that customer pressure fosters eco-innovation and high standards and requirements related to food safety.…”
Section: Int J Environ Res Public Health 2020 17 X 4 Of 19mentioning
confidence: 87%
“…On the other hand, the literature has argued that the use of fiscal incentives and subsidies fosters the introduction of eco-innovation, thus making its benefits higher than the costs of paying fines to governments for non-compliance [52]. Additionally, regulation has enabled the agri-food industry to address a prominent issue involving the processing of waste materials, as well as sustainable production systems [13].…”
Section: Int J Environ Res Public Health 2020 17 X 4 Of 19mentioning
confidence: 99%
See 1 more Smart Citation